2018
DOI: 10.1016/j.juro.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities to Decrease Radiation Exposure in Children with Renal Trauma

Abstract: Repeat computerized tomography in pediatric patients with renal trauma is common. Obtaining delayed imaging on the initial scan in patients with high grade renal trauma may prevent repeat scans. Renal ultrasound provides diagnostic usefulness in monitoring kidney injuries and should be considered before repeating computerized tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…20 However, other studies have shown that obtaining the delayed phase CT scans at initial imaging for any detected renal laceration may in fact reduce the number of follow up CT scans required. 21 This present study definitively argues for obtaining an on-table delayed excretory CT scan in the context of any renal laceration scored Grade 3 or higher, which captured all urine leaks in our larger series. Furthermore, we found that having CT imaging on arrival was closely associated with day one detection of urine leaks and more streamlined management.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…20 However, other studies have shown that obtaining the delayed phase CT scans at initial imaging for any detected renal laceration may in fact reduce the number of follow up CT scans required. 21 This present study definitively argues for obtaining an on-table delayed excretory CT scan in the context of any renal laceration scored Grade 3 or higher, which captured all urine leaks in our larger series. Furthermore, we found that having CT imaging on arrival was closely associated with day one detection of urine leaks and more streamlined management.…”
Section: Discussionsupporting
confidence: 52%
“…Some have questioned the necessity of obtaining CT imaging in pediatric renal trauma, with one study demonstrating that outcomes were not different between patients who had on-table delayed excretory CT and those who did not 20 . However, other studies have shown that obtaining the delayed phase CT scans at initial imaging for any detected renal laceration may in fact reduce the number of follow up CT scans required 21 . This present study definitively argues for obtaining an on-table delayed excretory CT scan in the context of any renal laceration scored Grade 3 or higher, which captured all urine leaks in our larger series.…”
Section: Discussionmentioning
confidence: 99%
“…The widely used ALARA (as low as reasonably achievable) principle is heavily emphasized in pediatrics to decrease unnecessary radiation exposure in all populations [11]. Regarding the reduction of radiation exposure in pediatric patients with renal trauma, evidence shows utilizing ultrasound for monitoring of renal trauma after obtaining diagnostic CT scan is an effective way to decrease radiation exposure [12,13]. In patients being treated for renal trauma at more than one institution by multiple providers, the ALARA principle may be compromised due to lower pediatric imaging protocol adherence or lack of outside hospital image transfer, leading to increased radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Renal trauma in the pediatric population is unique compared to adults. Increased risk for injury and complications due to the relative size and lack of rib protection of the pediatric kidneys, increased likelihood of undiagnosed congenital urogenital tract anomalies leading to complications, and the task of minimizing pediatric radiation exposure can present challenges in management [12,[14][15][16][17]. Although challenges differ from the those faced in the adult population, the 2019 Eastern Association for the Surgery of Trauma (EAST) pediatric blunt renal trauma practice management guidelines recommend nonoperative management with close monitoring for post-traumatic renal hypertension as the gold standard management for both adults and pediatrics [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Future research may reveal that repeat imaging of collecting system injury can be reasonably followed by ultrasound as urinoma is frequently picked up on ultrasonography. Indeed, a recent study investigating renal trauma in pediatric patients suggests that ultrasonography may be useful in evaluating renal trauma and beneficial in reducing unnecessary radiation [19]. In addition to limiting radiation, transition from CT scan to ultrasound could also reduce health care costs.…”
mentioning
confidence: 99%